George Shepley Locke and Susan Lucretia Hammond. - Unknown:::Creator::::::::::::
Portrait of Sarah Anne Jane Locke's parents, George Shepley Locke and Susan Lucretia Hammond with two unidentified women. Susan Lucretia Hammond is standing behind her husband.